Characterization of Microbial Population Shifts during Sample Storage - Mills, Heath J.; Kiel Reese, Brandi; St. Peter, Cruz (Frontiers in Microbiology, 2012)
The objective of this study was to determine shifts in the microbial community structure and potential function based on standard Integrated Ocean Drilling Program storage procedures for sediment cores. Standard long-term storage protocols maintain sediment temperature at 4oC for mineralogy, geochemical, and/or geotechnical analysis whereas standard microbiological sampling immediately preserves sediments at -80oC. Storage at 4oC does not take into account populations may remain active over geologic time scales at temperatures similar to storage conditions. Identification of active populations within the stored core would suggest geochemical and geophysical conditions within the core change over time. To test this potential, the metabolically active fraction of the total microbial community was characterized from IODP Expedition 325 Great Barrier Reef sediment cores prior to and following a three-month storage period. Total RNA was extracted from complementary 2, 20, and 40 m below seafloor sediment samples, reverse transcribed to cDNA and then sequenced using 454 FLX sequencing technology, yielding over 14,800 sequences from the six samples. Interestingly, 97.3% of the sequences detected were associated with lineages that changed in detection frequency during the storage period including key biogeochemically relevant lineages associated with nitrogen, iron and sulfur cycling. These lineages have the potential to permanently alter the physical and chemical characteristics of the sediment promoting misleading conclusions about the in situ biogeochemical environment. In addition, the detection of new lineages after storage increases the potential for a wider range of viable lineages within the subsurface that may be underestimated during standard community characterizations.